Diagnosis and immunosuppressive treatment of inflammatory cardiomyopathy: a case report. Issue 5 (3rd September 2021) - Naesens, L.; Penicka, M.; Heggermont, W.
ABSTRACT: Objectives : Definite diagnosis of myocarditis requires an endomyocardial biopsy (EMB) showing an inflammatory infiltrate. However, there are important limitations on establishing the diagnosis solely upon histological criteria. The main objective of this case report is to highlight the difficulty of diagnosis, but also to evaluate treatment in virus-negative inflammatory cardiomyopathy. Case report : We present the case of a 53-year-old man with an inflammatory cardiomyopathy based on cardiac magnetic resonance (CMR) findings consistent with extensive myocardial inflammation and a significantly depressed left ventricular ejection fraction (LVEF). Treatment with immunosuppressive therapy resulted in improvement of cardiac function and performance status, while also eliminating the need for ICD implantation. Conclusion : Cardiac magnetic resonance (CMR) has a high diagnostic accuracy and has become the primary diagnostic tool for noninvasive assessment of suspected myocarditis. EMBs should be analyzed using immunohistochemistry and viral polymerase chain reaction to increase the diagnostic sensitivity of histology. Immunosuppressive therapy should be considered in virus-negative inflammatory cardiomyopathy.